Perilaku Masyarakat Pinggiran Hutan terhadap Taman Nasional Kerinci Seblat di Kecamatan Gunung Tujuh - Agel Vidian Krama; Nurul Qamilah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to study the community about Kerinci Seblat National Park in Gunung Tujuh subdistrict about activities and negative activities conducted by the community towards Kerinci Seblat National Park. The research is a qualitative descriptive study, in decision informant with snowball technique. Means of collecting data using interviews, observation and documentation to obtain data on the study area. Data analysis technique is a technique performed Milles and Huberman model analysis of data reduction, data display, and conclusion. The results showed that: (1) A positive behavior forest fringe communities of the Kerinci Seblat National Park in the district of Gunung Tujuh: a) Communities in the District of Gunung Tujuh has prohibited if any of the members of the community who do clearing new land, b) People in Gunung Tujuh District have done reforestation. (2). These negative attitudes towards forest fringe communities Kerinci Seblat National Park in the district of Gunung Tujuh: a) People are still farming in the area of Gunung Tujuh, which belong to the zoning Kerinci Seblat National Park, b) Communities in the District of Gunung Tujuh they were cutting trees in the area of Kerinci Seblat National Park, c) Communities that have search as farmers and have pets, they took off their animals at the area Kerinci Seblat National Park, d) Public Gunung Tujuh still throwing objects which can damage TNKS area, e) Community Gunung Tujuh still hunting animals in Kerinci Seblat National Park. f) People who work as farmers have been doing selective in making wood contained in the Kerinci Seblat National Park. Conclusion Before the existence of the KSNP community, they were already earning a living as farmers and with the presence of the KSNP community behaved positively by preserving the TNKS preservation but there were still people who behaved negatively due to the necessity of life. Keywords: Community, Behavior